Spinal Anesthesia with Ultrasonography (USG) Marker in Morbidly Obese Pregnant Women Undergoing Cesarean Section Surgery: A Case Report - Parama Adi, Made Septyana; I Gusti Ngurah Mahaalit Aribawa; I Gusti Agung Gede Utara Hartawan; I Putu Fajar Narakusuma; Gusti Agung Made Wibisana Kurniajaya (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Spinal anesthesia is a regional anesthesia technique used to provide analgesia or numbness in the lower part of the body. This technique has long been employed in childbirth and cesarean section surgeries due to its numerous advantages for pregnant women. Obese pregnant patients often have increased adipose tissue in the back area, making it challenging to identify the appropriate interspinous space. Case presentation: A 26-year-old primigravida at 38 weeks of gestation with morbid obesity, standing at 158 cm tall and weighing 140 kg, with a body mass index (BMI) of 56.1 kg/m², underwent cesarean section surgery under spinal anesthesia. The identification of the spinal needle insertion site was performed using pre-procedural ultrasound (USG) marker at the L3-L4 level, with heavy bupivacaine 0.5% 12.5 mg used as the anesthetic agent. The surgery lasted for 1 hour and 20 minutes, with stable hemodynamics and a blood loss of 450 ml. A female infant was delivered, weighing 3080 grams, with a length of 50 cm and an APGAR score of 8-9-10. Conclusion: The use of USG markers can assist in determining the precise location for spinal anesthesia injection, thereby reducing complications from repeated needle insertions.